Religion and the new atheism : a critical appraisal - Amarnath Amarasingam (Studies in critical social sciences ;, 2010)
The term new atheism has been given to the recent barrage of bestselling books written by Richard Dawkins, Sam Harris, Daniel Dennett, Christopher Hitchens, and others. These books and their authors have had a significant media presence and have only grown in popularity over the years. This book brings together scholars from religious studies, science, sociology of religion, sociology of science, philosophy, and theology to engage the new atheism and place it in the context of broader scholarly discourses. This volume will serve to contextualize and critically examine the claims, arguments and.